The Teaching of Botany at the basic education: perceptions and analysis of a teaching strategy (Research, Society and Development, 2020)
The present work presents the results of an investigation of the perceptions about the Plant Diversity of 26 students of the sixth grade of Elementary School in a public school in the city of Uruguaiana/RS. The objectives of this work were to investigate the prior knowledge of students in the sixth year of elementary school regarding the concepts of living beings and plants and to propose a pedagogical action, which would collectively promote discussions about the Teaching of Botany and the reframing of concepts based on in mediation of content. The methodology used was the five steps of the Historical-Critical Pedagogy of Dermeval Saviani, and the productions of the investigated, drawings, interviews and activities were characterized as object of analysis, according to Bardin (2011). The results obtained evidenced that the human being represents the previous conception of being alive of the majority of the students, being the conception of vegetables turned only to the feeding. It was verified that although Vegetal Diversity is very close to students in daily life, they don’t know how to name their basic structures and functions. There was no increase in knowledge regarding the concept of vegetables, however there was an appropriation of the concept of living being much more comprehensive in the final social practice.